Implementasi Pembiasaan Ucapan Islami Harian dan Respon Siswa di Tadika Brilliant Buds Edukids - Yulia Rahma; Mavianti (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2025)
This study is motivated by the need for Islamic character building in early childhood through hidden curriculum amid modern moral challenges, focusing on Tadika Brilliant Buds Edukids. The objectives are to describe the implementation of daily Islamic greetings habituation, student responses, and supporting-inhibiting factors. Employing descriptive phenomenological qualitative approach with data triangulation via participatory observation, in-depth interviews, and documentation. Population includes 56 students aged 4-6 years across three classes, three teachers, and one manager, selected via purposive sampling. Main instrument is the researcher with observation-interview guidelines, analyzed using Miles-Huberman model and NVivo thematic analysis. Findings reveal structured implementation yielding 70% positive spontaneous responses, supported by teacher exemplarity and religious environment, yet hindered by curriculum time constraints and monotony. Conclusion affirms behaviorism's effectiveness for moral internalization, recommending method innovations and parental collaboration.